2003
DOI: 10.1186/1471-2407-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Activity and expression of progesterone metabolizing 5α-reductase, 20α-hydroxysteroid oxidoreductase and 3α(β)-hydroxysteroid oxidoreductases in tumorigenic (MCF-7, MDA-MB-231, T-47D) and nontumorigenic (MCF-10A) human breast cancer cells

Abstract: BackgroundRecent observations indicate that human tumorous breast tissue metabolizes progesterone differently than nontumorous breast tissue. Specifically, 5α-reduced metabolites (5α-pregnanes, shown to stimulate cell proliferation and detachment) are produced at a significantly higher rate in tumorous tissue, indicating increased 5α-reductase (5αR) activity. Conversely, the activities of 3α-hydroxysteroid oxidoreductase (3α-HSO) and 20α-HSO enzymes appeared to be higher in normal tissues. The elevated convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 45 publications
5
70
1
1
Order By: Relevance
“…The on-going studies in our laboratories indicate that diols bind with low affinity to the human androgen receptor (hAR) and induce very limited hAR-mediated transactivation, particularly the 3a,5a-diol (A E Lemus, P Damian-Matsumura, R GarciaBecerra, L Gonzalez, D Orolaz, F Larrea & G Perez, Unpublished observations). The finasteride-induced inhibition of DHTand diols formation in MCF-7 cells, as demonstrated in this study, may have additional interest, since various locally formed A-ring-reduced metabolites of progesterone , Wiebe & Muzia 2001, Wiebe & Lewis 2003 are capable of inducing cell proliferation in human breast cancer, through a novel, non-genomic mechanism (Weiler & Wiebe 2000). The overall results demonstrated that finasteride inhibits the formation of oestrogenic steroids (diols) generated downstream of DHT, as suggested recently by Ishikawa et al (2006).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The on-going studies in our laboratories indicate that diols bind with low affinity to the human androgen receptor (hAR) and induce very limited hAR-mediated transactivation, particularly the 3a,5a-diol (A E Lemus, P Damian-Matsumura, R GarciaBecerra, L Gonzalez, D Orolaz, F Larrea & G Perez, Unpublished observations). The finasteride-induced inhibition of DHTand diols formation in MCF-7 cells, as demonstrated in this study, may have additional interest, since various locally formed A-ring-reduced metabolites of progesterone , Wiebe & Muzia 2001, Wiebe & Lewis 2003 are capable of inducing cell proliferation in human breast cancer, through a novel, non-genomic mechanism (Weiler & Wiebe 2000). The overall results demonstrated that finasteride inhibits the formation of oestrogenic steroids (diols) generated downstream of DHT, as suggested recently by Ishikawa et al (2006).…”
Section: Discussionmentioning
confidence: 52%
“…These results confirm and extend the report of Wiebe et al (2000), who, using radiolabelled progesterone as substrate, demonstrated an enhanced 5a-steroid reductase activity and also an overexpression of the 5a-steroid reductase type-1 gene in MCF-7 cells, as compared with oestrogen-resistant breast cells (MCF-10A). Furthermore, Wiebe & Lewis (2003) Steroid competitor (nM) Figure 7 Binding affinities of 3a,5a-and 3b,5a-androstanediols (diols) to human oestrogen receptors (hER). Cytosol aliquots of HeLa cells transfected with either hERa or hERb gene expression vectors were incubated with 1 nM [ 3 H] oestradiol at 4 8C, for 48 h, in the absence or presence of increasing concentrations of radioinert 3a,5a-diol, 3b,5a-diol and oestradiol (E 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 4-pregnenes can be further reversibly converted to 4-pregnene-3a(3b),20a-diol. The same metabolic pathways were subsequently demonstrated in four different breast cell lines (Wiebe & Lewis 2003) and had been previously identified in a number of tissues, including gonads, pituitary, and hypothalamus (Wiebe 1997). In addition, in the human breast cell lines, the final major product was 5a-pregnane-3b,6a-diol-20-one, indicating the presence of 6a-hydroxylase, an enzyme that was also present in tissues at minor activity levels.…”
Section: Progesterone Is Metabolized By Many Tissuesmentioning
confidence: 71%
“…Furthermore, using co-transfected cell expression systems, we have shown that non-phenolic reduced metabolites of 19-norprogestins are able to transactivate estrogen-dependent genes mediated through human ERa, but not through ERb (Larrea et al 2001, García-Becerra et al 2002, behaving as selective ERa modulators, with ligand-receptor structural and functional responses similar to those induced with naturally occurring E 2 . Additional studies on the effects of progestin reduced derivatives on breast tissue are required, particularly since an overexpression of the 5a-steroid reductase type 1 gene has been reported in breast cancer tumors and cells (Suzuki et al 2001, Wiebe & Lewis 2003.…”
Section: Discussionmentioning
confidence: 99%